2020
DOI: 10.1177/0956247820922843
|View full text |Cite
|
Sign up to set email alerts
|

Local response in health emergencies: key considerations for addressing the COVID-19 pandemic in informal urban settlements

Abstract: This paper highlights the major challenges and considerations for addressing COVID-19 in informal settlements. It discusses what is known about vulnerabilities and how to support local protective action. There is heightened concern about informal urban settlements because of the combination of population density and inadequate access to water and sanitation, which makes standard advice about social distancing and washing hands implausible. There are further challenges to do with the lack of reliable data and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
236
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(265 citation statements)
references
References 21 publications
2
236
0
7
Order By: Relevance
“…Interestingly, Hamidi et al (2020) have reported that at county level in the USA, population density is not significantly related to infection rate possibly because of adherence to social distancing. In low-and middle-income countries though, high population density is commonly associated with informal urban settlements, being social distancing impracticable (Wilkinson 2020). The sensitivity analysis indicated the importance of the average income and the gross domestic product within the expanded metropolitan area of São Paulo, Brazil (Table 3) possibly due to higher frequency of international traveling of population living in wealthier neighborhoods.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, Hamidi et al (2020) have reported that at county level in the USA, population density is not significantly related to infection rate possibly because of adherence to social distancing. In low-and middle-income countries though, high population density is commonly associated with informal urban settlements, being social distancing impracticable (Wilkinson 2020). The sensitivity analysis indicated the importance of the average income and the gross domestic product within the expanded metropolitan area of São Paulo, Brazil (Table 3) possibly due to higher frequency of international traveling of population living in wealthier neighborhoods.…”
Section: Resultsmentioning
confidence: 98%
“…6 7 While tight restrictions on movement may contribute to reduced disease transmission, there are social and economic consequences of locking down slums and the impact on access to healthcare. [8][9][10] It is the latter that we focus on in this paper. Effective public health strategies in slums cannot overlook the perspectives, insights and solutions offered by those who must work and live with them.…”
Section: Introductionmentioning
confidence: 99%
“…Effective public health strategies in slums cannot overlook the perspectives, insights and solutions offered by those who must work and live with them. [8][9][10] Our study forms part of the NIHR Global Health Research Unit on Improving Health in Slums, a multipartner, multimethod collaboration 11 exploring healthcare and access in seven slums in Bangladesh, Kenya, Nigeria and Pakistan. Although the term 'slum' is widely debated, for this paper, we define a slum as an area of high population density that lacks sanitation, clean water, safe and durable housing, as well as basic services.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of COVID-19, characterizing the spatio-temporal burden of diseases at a community scale provides critical support to city authorities and community-based organizations for the development of targeted strategies to minimize virus transmissions and provide better healthcare. This problem is not specific to the COVID-19 pandemic, as UN-Habitat also acknowledges that, within cities, there is a "lack of data" on deprived areas that do not allow for effective responses to most emergencies [14]. Data on such areas often lack reliability and information about the number of people, along with their health conditions.…”
Section: Introductionmentioning
confidence: 99%